Portal vein arterialization as a salvage procedure in hepatopancreatobiliary surgery: a systematic review - Majlesara, Ali; Ghamarnejad, Omid; Khajeh, Elias; Golriz, Mohammad; Soleymanzadeh Gharabaghi, Negin; Hoffmann, Katrin; Chang, De-Hua; Büchler, Markus W.; Mehrabi, Arianeb (Canadian journal of surgery, 2021)
Background: Portal vein arterialization (PVA) is a possible option when hepatic artery reconstruction is impossible during liver resection. The aim of this study was to review the literature on the clinical application of PVA in hepatopancreatobiliary (HPB) surgery. - Methods: We performed a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We systematically searched the PubMed, Embase and Web of Science databases until December 2019. Experimental (animal) studies, review articles and letters were excluded. - Results: Twenty studies involving 57 patients were included. Cholangiocarcinoma was the most common indication for surgery (40 patients [74%]). An end-to-side anastomosis between a celiac trunk branch and the portal vein was the main PVA technique (35 patients [59%]). Portal hypertension was the most common longterm complication (12 patients [21%] after a mean of 4.1 mo). The median followup period was 12 (range 1-87) months. The 1-, 3- and 5-year survival rates were 64%, 27% and 20%, respectively. - Conclusion: Portal vein arterialization can be considered as a rescue option to improve the outcome in patients with acute liver de-arterialization when arterial reconstruction is not possible. To prevent portal hypertension and liver injuries due to thrombosis or overarterialization, vessel calibre adjustment and timely closure of the anastomosis should be considered. Further prospective experimental and clinical studies are needed to investigate the potential of this procedure in patients whose liver is suddenly de-arterialized during HPB procedures.